2017
DOI: 10.1039/c7dt00400a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and photocatalytic behavior of 2,9-di(aryl)-1,10-phenanthroline copper(i) complexes

Abstract: The synthesis, photophysical properties, and theoretical calculations of 2,9-di(aryl)-1,10-phenanthroline copper(i) complexes are described along with application to a photocatalytic ATRA reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 149 publications
(52 reference statements)
1
27
0
Order By: Relevance
“…[15][16][17][18] The pioneering work of Sauvage and co-workers with Cu(dap)2Cl [19] as photoredox catalyst was published in 1987, [20] but apart from some contemporary publications, [21] only recently have Cu(I) complexes been applied as photoredox catalysts or photosensitizers (PS). [22][23][24][25][26][27][28][29][30][31][32] In artificial photosynthesis [33,34] the photosensitizer absorbs the luminous radiation and transfers the energy to a catalyst, which then activates the small molecule (usually either water or carbon dioxide). The characteristics that a PS should have are the following: good absorption in the visible light region, long-lived excited state, and high stability.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The pioneering work of Sauvage and co-workers with Cu(dap)2Cl [19] as photoredox catalyst was published in 1987, [20] but apart from some contemporary publications, [21] only recently have Cu(I) complexes been applied as photoredox catalysts or photosensitizers (PS). [22][23][24][25][26][27][28][29][30][31][32] In artificial photosynthesis [33,34] the photosensitizer absorbs the luminous radiation and transfers the energy to a catalyst, which then activates the small molecule (usually either water or carbon dioxide). The characteristics that a PS should have are the following: good absorption in the visible light region, long-lived excited state, and high stability.…”
Section: Introductionmentioning
confidence: 99%
“…30,45,[49][50][51][52][53][54][55] Recent studies have shown that Cu(I) complexes containing one diimine ligand, and one diphosphine ligand such as 4,5-bis(diphenylphosphino)-9,9dimethyl-xanthine (xantphos), which has a large bite angle and high steric hindrance, can have even longer excited state lifetimes (ns-ms). [56][57][58][59][60] Cu(I) complexes are being increasingly used as photosensitisers in photocatalysis, 24,25,30,51,[61][62][63][64][65][66][67][68][69][70][71][72][73] and dyes-sensitised solar cells. 74 They are also used as antitumor [75][76][77][78] and antibacterial agents [79][80][81][82][83][84][85] due to their innate dark toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Emission of Cu(I) based complexes in fluid solution under air is quenched by the presence of O 2 while no emission is observed in degassed ethanol due to Lewis base quenching . Although substitution of 1,10‐phenanthroline at the 2 and 9 positions usually affords protection of Cu(I) from quenching by weakly coordinating solvents, and even in degassed CH 2 Cl 2 , a typically non‐coordinating solvent, the MLCT emission is too weak to observe for any of these complexes. Previous researchers have noted for bis ‐phenanthroline as well as mixed‐ligand compounds that coordinating solvents and various gaseous ligands such as CO can surprisingly displace phenanthroline ligands, even though they are chelated to the Cu(I) center .…”
Section: Resultsmentioning
confidence: 99%
“…The syntheses of all metal complexes were accomplished by addition of the corresponding metal salts to a solution of dmesp ligand in either a dry solvent mixture of MeCN:CH 2 Cl 2 (50:50) or dry CH 2 Cl 2 . The synthetic procedures are summarized below (Scheme ).…”
Section: Resultsmentioning
confidence: 99%